COMPLEX INVESTIGATIONS OF THERMALPHYSIC AND INFRA-RED CHARACTERISTICS AT THE PHASE INVERSIONS - V. L. Dragun; N. I. Stetukevich; V. F. Shevtsov; M. V. Hilko (Литьë и металлургия)
The complex methods of investigation of heat exchange at crystallization and melting of selectively transparent materials in terms of changing of external heat influences, which include calorimetry of IK-currents, temperature taking, the heat conduction coefficient, ultrasound speed, are developed. The IK-methods of control of the melting and crystallization kinetics are approved. The data on measuring of integral current of IK-radiation, temperature, the heat conduction coefficient, ultrasound speed of the samples of working substances in terms of melting and crystallization are analysed.